Spolna zloraba otrok - Maleš, Andreja (Obzornik zdravstvene nege, 2000)
The article presents the results of a research dealing with the problems of abused children in the frames of work of community nurses. Sixty community nurses from the regions of Ljubljana, Kamnik and Domžale have been investigated. The hypothesis that community nurses often encounter sexual abuse during their fieldwork has been proven. According to the results of the questionnaire, one fourth of the investigated nurses have encountered with sexual abuse. However, the fact that one fourth of the investigated nurses have received no training from sexual abuse, is in our opinion worrying.
Keywords: child; medicinske sestre; otroci; patronažna služba; spolna zloraba; zdravstvena nega